(untitled) (Plant Tissue Culture and Biotechnology, 2015)
The objective of the current study was to assess and establish intraspecific variation between three morphotypes of Cissus quadrangularis using ten Consensus Chloroplast Microsatellite Primers. Significant level of genetic variation was detected between the three morphotypes. Sequence analysis of the CCMP PCR fragment showed the high degree of similarity to the chloroplast genome sequences of other Vitaceae members indicating that these regions are highly conserved. Plant Tissue Cult. & Biotech. 24(2): 205-212, 2014 (December)